1987
DOI: 10.3171/jns.1987.66.6.0865
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-based stereotaxic serial biopsies in untreated intracranial glial neoplasms

Abstract: Forty patients with previously untreated intracranial glial neoplasms underwent stereotaxic serial biopsies assisted by computerized tomography (CT) and magnetic resonance imaging (MRI). Tumor volumes defined by computer reconstruction of contrast enhancement and low-attenuation boundaries on CT and T1 and T2 prolongation on MRI revealed that tumor volumes defined by T2-weighted MRI scans were larger than those defined by low-attenuation or contrast enhancement on CT scans. Histological analysis of 195 biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
315
0
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 718 publications
(329 citation statements)
references
References 23 publications
7
315
0
7
Order By: Relevance
“…Confirmation of this analogy has been provided by Silbergeld and Chicoine (1997), who were able to grow in culture glioma cells from brain tissue that was histologically normal 4 cm distal to the gross edge of the tumour. Furthermore, Kelly et al (1987) were able to show in at least half of their patients that 'isolated tumour cells' could be identified microscopically in biopsies distal to even the most sensitive MRI marker. Previous reports (Burgess et al, 1997) estimated the enhanced CT-delineated tumour boundary to correspond to a tumour cell concentration of about 8000 cells mm 73 .…”
Section: Thresholds Of Detectionmentioning
confidence: 99%
“…Confirmation of this analogy has been provided by Silbergeld and Chicoine (1997), who were able to grow in culture glioma cells from brain tissue that was histologically normal 4 cm distal to the gross edge of the tumour. Furthermore, Kelly et al (1987) were able to show in at least half of their patients that 'isolated tumour cells' could be identified microscopically in biopsies distal to even the most sensitive MRI marker. Previous reports (Burgess et al, 1997) estimated the enhanced CT-delineated tumour boundary to correspond to a tumour cell concentration of about 8000 cells mm 73 .…”
Section: Thresholds Of Detectionmentioning
confidence: 99%
“…Following contrast agent extravasation, tumor regions become bright on T1-weighted images due to T1 shortening. Studies have confirmed that areas of contrast enhancement often contain the most aggressive portions of the tumor [4], suggesting the presence of contrast-enhancement reflective of increased vascular permeability may be a valuable surrogate for more aggressive brain tumor behavior. In 1990, Macdonald et al [5] introduced the first response criteria specifically for neuro-oncology by specifying the definition of radiographic response using quantitative bidirectional measurements and accounting for corticosteroid use and neurological status.…”
Section: Introductionmentioning
confidence: 98%
“…Serial biopsy studies show tumor cells more than 3 cm from the contrast enhancing (CE) region [13]; in addition, some tumors are not contrast-enhancing, and the T2 hyperintensity (T2h) may not distinguish tumor from edema, or normal appearing brain tissue beyond T2h might harbor tumor cells. Previous studies have shown that threedimensional (3D) magnetic resonance spectroscopic imaging (MRSI) is valuable for mapping the spatial extent of brain tumors and this technique is suggested as an adjunct to MRI in delineating the target for radiation therapy in high-grade gliomas (HGG) [14,15].…”
Section: Introductionmentioning
confidence: 99%